Production of Personal Records in Sexual Offences Trials - Pithey, Bronwyn (Institute of Criminology, 2014)
This paper will investigate the position of disclosure of personal records in other jurisdictions and will discuss the lack of specific legislation on this issue in South Africa. It will also explore legal options available for complainants and record holders to resist the disclosure of this information as well as the rationale of the defence and the courts in admitting this information into evidence as relevant. The paper will attempt to reveal the flawed reasoning of the defence and the courts in justifying the use of personal records of complainants by investigating the myths and stereotypes about women, children and sexual assault that inform this reasoning, and will recommend how government must intervene to combat this phenomenon to ensure real protection of women and children in the criminal justice system.